Antibiotic sensitivity pattern in urinary tract infection among adults in central part of Nepal - Sedhain, Arun; Sapkota, Abja; Shrestha, Bidhan (Journal of Chitwan Medical College, 2019)
Background: Urinary tract infection (UTI) is characterized by pathological invasion of the urinary tract by microorganisms. Majorities of organisms causing UTI are gram negative bacteria, most common of which is E. coli. Urine culture and sensitivity test is used to isolate the organism and to identify the susceptible drug of choice for appropriate treatment. This hospital-based study was carried out to analyze the spectrum and antibiotic susceptibility of microorganisms causing UTI. Methods: A retrospective study was done to analyze the results of urine culture and sensitivity test done at Chitwan Medical College Teaching Hospital over a period of two and half years. Standard guideline and protocol were used to collect the urine sample and to perform the test. Data analysis was done using SPSS version 21.0. Result: Out of 12, 925 urine samples submitted for culture and sensitivity test during the study period, bacterial pathogens were isolated from 3, 173 (24.54%) samples, which was significantly higher among females (28%) than the males (17%). The most common organism isolated on the culture was E. coli (68.5%) followed by Klebsiella (18.4%). Sensitivity of the uropathogens was seen highest with colistin (79.2%) followed by teicoplanin (64.58%), Aztreonam (63.25%) and Nitrofurantoin (61.16%). Most common antibiotics that showed resistance to the microorganisms in this study were Ampicillin (60.93%), Cotrimoxazole (53.72%), Cefixime (40.57%) and Levofloxacin (32.93%). Conclusions: This study has found a usual pattern of UTI with higher prevalence among females and E. coli being the most common organism. Nitrofurantoin has been found to have a good susceptibility for the treatment of UTI.